Adaptation to stressors: hormesis as a framework for human performance - Hill, Yannick; Kiefer, Adam W.; Oudejans, Raôul R. D.; Baetzner, Anke; Den Hartigh, Ruud J. R. (New ideas in psychology, 2024)
Although stressors are frequently linked to several negative health outcomes, experiencing stressors may be necessary for enhancing performance. At present, the literature is lacking a unified, comprehensive framework that accounts for both positive and negative outcomes following stressors. Therefore, we introduce the framework of hormesis, which has been applied in biological research for decades. According to hormesis, small-to-medium doses of a stressor can stimulate an organism's response, while large doses cause detrimental effects. In this article, we argue that these dose-response dynamics can be found in various domains of performance psychology (i.e., eustress and distress, psychological momentum, emotions, motivation, confidence, cognitive performance, training, skill acquisition, adversity, and trauma). Furthermore, hormesis also accounts for the inter- and intra-individual variability commonly found in responses to stressors. Finally, from an applied perspective, leveraging hormesis may stimulate new psychological interventions that mimic the well-known effects of (toxic) vaccinations at the level of behavior.
Gesehen am 30.07.2024